Teachers’ Role In Introducing Sexual Education Through Art To Early Childhood At RAB Perwanida Bendunganjati Pacet Mojokerto (Efforts To Prevent Sexual Harassment In Early Childhood) - Jihan Kusuma; Amalia Rahmawati (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2023)
Sexual harassment is a serious matter that will damage a child's future both in the short and long term. The consequences do not only affect the victims, but also their parents, families and economics. Indonesia’s current condition about this is very concerning where every year there is a lot of data that collects cases of sexual harassment and is not taken seriously. This has become a concern for parents and the public. Sexual harassment occurs due to the lack of knowledge of parents regarding sexual education for children and they only rely on sexual education in schools. However, sexual education in schools is rarely considered and implemented. Based on the background, this study discusses teachers’ role in introducing sexual education to early childhood at RA B Perwanida Bendunganjati Pacet Mojokerto (Efforts to Prevent Sexual Harassment in Early Childhood). The purposes of this study were to analyze (1) parents’ role in sexual education for early childhood. (2) Teachers’ role in introducing sexual education to students. (3) The media used by the teacher to facilitate the sexual education material. By employing qualitative research, this study was conducted in RA Purwanida group B with 18 students as subjects, one student guardian, and two teachers. The data in this study were carried out through 3 stages: Reduction, Data Presentation, and Documentation. The results of this study indicate that (1) Parents have provided sexual education to early childhood when they are at home. (2) The teacher has played a role in introducing sexual education through the media of images and singing methods. (3) Learning the sexual education in early childhood is more effective if it is explained concretely.